Dietary Behavior and Physical Activity in Children and Adolescents - Hebestreit, Antje (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In recent years, diet- and lifestyle-related disorders have become a major health threat in Europe and worldwide. The contributions in this monograph include 2 review articles and 19 original contributions from several countries that provide new information on the existing research elucidating important aspects of children's and adolescents' nutrition and lifestyle behavior. The data included in this Special Issue are from large epidemiological studies, including several multicenter and multinational studies, as well as datasets from surveillance initiatives. The topics of interest of this Special Issue include the co-occurrence of multiple health behaviors in children, the role of parenting and early feeding practices, dairy consumption in childhood, validity of dietary intake data, dietary supplement use in children, as well as socioeconomic disparities and eating culture. The diverse articles in this Special Issue highlight the complexity and extent to which nutrition and physical activity behaviors may influence different health aspects of children and adolescents. As seen by the various findings and recommendations, not only is more work in this area required but the translation of this work to practice and policy is imperative if we are to address the challenges impacting the nutrition, physical activity, and health of young populations.